Thermal infrared image processing to assess heat generated by magnetic nanoparticles for hyperthermia applications - Rodrigues, Raquel Oliveira (2016)
Magnetic fluid hyperthermia (MFH) is considered a promising therapeutic technique for the treatment of cancer cells, in which magnetic nanoparticles (MNPs) with superparamagnetic behavior generate mild-temperatures under an AC magnetic field to selectively destroy the abnormal cancer cells, in detriment of the healthy ones. However, the poor heating efficiency of most NMPs and the imprecise experimental determination of the temperature field during the treatment, are two of the majors drawbacks for its clinical advance. Thus, in this work, different MNPs were developed and tested under an AC magnetic field (~1.10 kA/m and 200 kHz), and the heat generated by them was assessed by an infrared camera. The resulting thermal images were processed in MATLAB after the thermographic calibration of the infrared camera. The results show the potential to use this thermal technique for the improvement and advance of MFH as a clinical therapy.